Durability and Self-Sealing Examination of Concretes Modified with Crystalline Waterproofing Admixtures - Pejman Azarsa (MDPI AG, 2021)
Repairing concrete structures costs billions of dollars every year all around the globe. For overcoming durability concerns and creating enduring economical structures, chemical admixtures, as a unique solution, have recently attracted a lot of interest. As permeability of a concrete structure is considered to play a significant role in its durability, Permeability Reducing Admixtures (PRA) is one of the ideal solutions for protecting structures exposed to water and waterborne chemicals. Different products have been developed to protect concrete structures against water penetration, which, based on their chemistry, performance, and functionality, have been categorized into PRA. As it has previously been tested by authors and proven to be a promising solution, a hydrophilic Crystalline Waterproofing Admixtures (CWA) has been considered for this study. This paper aims to investigate how this product affects concrete’s overall freeze–thaw resistance, self-sealing, and corrosion resistance. Various testing methods have been utilized to examine the performance of CWA mixtures, including the linear polarization resistance, resonance frequency testing, half-cell potential, and self-sealing test. The reinforcement corrosion potential and rate measurements indicated superior performance for CWA-treated samples. After being exposed to 300 freeze–thaw cycles, concrete mixes containing CWA—even non-air-entrained ones—showed a Durability Factor (DF) of more than 80% with no signs of failure, while non-air-entrained control samples indicated the lowest DF (below 60%) but the greatest mass loss. The major causes are a reduction in solution permeability and lack of water availability in the concrete matrix—due to the presence of CWA crystals. Furthermore, evidence from the self-sealing test suggests that CWA-treated specimens can seal wider cracks and at a faster rate.